Marine Research in Modern Law of the Sea: LOSC and Reality - Bourtzis, Tilemachos; Rodotheatos, Gerasimos (The International Hydrographic Review, 2012)
Marine Research has proved to be one of the most controversial legal topics in terms of practice. While Law of the Sea Convention (LOSC) contains a special Part (XIII) on Marine Scientific Research, it fails to regulate topics of dual, ambiguous and/or evolving content. The current paper makes an inquiry into those topics (e.g. Military Surveys, Marine Archaeology, Remote Sensing) and tries to identify problems or gaps. These activities can have an extremely large footprint as they are connected with State and financial interests. The consequences of allowing marine research activities to proceed without solid rules could be grave. It is of extreme importance that each of the activities mentioned in this paper should have a clear set of rules of conduct.